Kualitas sebagai Pemediasi Pengaruh Strategi Kompetitif Kepemimpinan Biaya terhadap Kinerja Perusahaan - Soni Kurniawan, Ignatius (Widya Warta, 2013)
This paper examines the relationship among cost leadership competitive strategy, manufacturingÂ  strategy, Â and Â ï¬rm Â performance Â of Â manufacture Â firms Â in Â the Â Jababeka Industrial Estate, West Java. The sample was taken by applying a non-probability method with a purposive sampling technique. The questionnaires processed were 104 in number; 79 of which were obtained from mail survey and 25 from e-mail survey. The data were analyzed by making use of path analysis technique. The finding showed that there was signiï¬cant and positive relationship among cost leadership competitive strategy and the manufacturing strategies of ï¬‚exibility, quality, delivery, and low cost. It also confirmed that the quality was the only manufacturing strategy component that inï¬‚uences firm performance. The further result showed that the quality mediated a relationship between cost leadership competitive strategies and firm performance.